Implementasi Prinsip-Prinsip Hukum Islam dalam Layanan Umroh pada KBIH Al Huda Tarogong Kaler Kabupaten Garut - RofiahAlawiyah, Kiki; Gaussian, Gini; IipSyaripudin, Enceng (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2026)
This study is motivated by the increasing public interest in performing Umrah, accompanied by the growth of Hajj Guidance Groups (KBIH). This condition requires assurance that the services provided are in accordance with Islamic legal principles, particularly in aspects of contracts (akad), transparency, justice, and accountability. This study aims to analyze the implementation of Islamic legal principles in Umrah services at KBIH Al Huda Tarogong Kaler, Garut Regency. This research employs a qualitative method with a descriptive-analytical approach. Data were collected through observation, interviews with administrators and pilgrims, and documentation related to the implementation of Umrah services. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, referring to Islamic legal principles in the field of muamalah. The results show that the implementation of Islamic legal principles in Umrah services at KBIH Al Huda has generally been well executed, as indicated by clear contractual agreements, cost transparency, and guidance services oriented toward the welfare of pilgrims. However, improvements are still needed in the socialization of contracts and the strengthening of administrative aspects of services in order to enhance pilgrims’ trust and satisfaction.